Desenvolvimento da carcinicultura marinha familiar no agreste de alagoas : avanços e desafios para uma produção sustentável - Lemos, Fernanda Gomes (2023)
In Brazil, for many years, the production of marine shrimp was associated with estuarine, apicum, and mangrove regions. However, the last few years have been marked by a pronounced expansion to inland regions, an activity known as marine carciniculture. In the state of Alagoas, Northeast of Brazil, the harsh climate region has the newest Brazilian centers of Litopenaeus vannamei shrimp production in continental waters: Arapiraca, Craíbas, Coité do Nóia, Feira Grande, Girau do Ponciano, Igaci, Lagoa da Canoa, Limoeiro de Anadia, Olho D'Água Grande and Taquarana. For these municipalities, the activity emerged as an alternative for generation of employment and income for farmers who suffered and still suffer with the decline of agricultural production due to the disuse of land, by the salinization of water from rivers, creeks, and artesian wells. As it is relatively recent in the region, there are few records about its implementation. In view of this, the objective was to characterize the carciniculture in the harsh climate region of Alagoas by the investigation of its participants and its ways of production. To accomplish this task, 40 family farmers were interviewed by using a semi-structured questionnaire. In addition, free observations were made and informal accounts were collected during the years 2020 to 2022. From this, it was found that local carciniculture started a little over three years ago and only in 2018 gained commercial character having presented annual income of up to $ 300,000.00. The activity in the municipalities of Alagoas has been done with the help of technical advice, and with the construction pattern of nurseries from other production centers, similar to the systems implemented in the state of Paraíba. The farmers, with the help of professionals and knowledge acquired over time, have adapted to the new productive activity, when comparing the methodology implemented in harsh climate region of Alagoas with other regions, is possible to identify peculiarities, the ties and bonds created between those involved and the work environment. Some curiosities also draw attention, such as the variations in stocking densities observed in different poles, something common in all poles is the decrease in stocking density in rainy periods, high rainfall that resulted in decreased water temperature, which can contribute to the proliferation of pathogens in the culture environment. The analysis of the questionnaires showed that male family farmers represent 82.5% of the total of producers in the harsh climate region, while women correspond only to 17.5%. Both sexes work in the activity, on average, 8 hours a day. The size of the evaluated farms varies between 1 to 50 hectares, and the ponds built on them are between 1000 m2 and 4000 m2, with an average production of 500 kg to 4500 kg per month per farm. The price per kilogram of shrimp sold varied between $ 12.51 and R$ 13.64, being influenced by the time of the year, among other factors. It was evidenced that the poles with greater productive relevance are: Arapiraca, Coité do Nóia, Igaci and Limoeiro de Anadia. Among the interviewees, few (17.5%) have carciniculture as their main source of income, in their majority, the family farmers diversify the agricultural production to get enough income for subsistence. From the interviews, it was possible to identify that more than 50% of the owners received technical assistance in the last year. Since this is a fairly new activity, it is still not known for sure which impacts or environmental damage may be caused in the long term by the activity in this region. In this sense, most of the family farmers affirm that they have never been visited by environmental inspection agencies. Despite this, all are aware of the importance of environmental licensing and claim to be a significant step for shrimp production. Regarding the discharge of effluents, most (55%) of the farmers perform water treatment before discharge into water bodies. However, most family farmers (80%) do not consider the water generated from the ponds harmful to the environment. In fact, technical assistance was one of the key factors for the consolidation and success of the productive activity in the region. It was possible to observe from the farmers' reports how starting with technical assistance made all the difference. The data collected from the interviewees were compared with the data collected from the secretaries, it was possible to notice that the environmental and governmental organs linked to the carciniculture activity still don't have, or in their majority, with limited information, what can have repercussions, directly, in a negative way, in the development of public policies directed to marine Carciniculture. In addition, it is possible to verify the existence of barriers to the strengthening of the activity, being the issues related to environmental licensing the most relevant, among them: difficulties in finding qualified professionals to perform the services, the high fees charged, the slowness of the environmental inspection agencies.